1993
DOI: 10.1093/rheumatology/32.12.1044
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Like Particles in Synovial Fluids From Patients With Rheumatoid Arthritis

Abstract: Based on the elevated expression of oncogenes in proliferating transformed-appearing synoviocytes we searched for the possible involvement of a viral agent in the pathogenesis of RA. We report the detection of virus-like particles with retroviral C type morphology in SF, which lack the typical morphologic as well as immunohistochemical features of the human T-lymphotropic and immunodeficiency viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 0 publications
1
24
0
2
Order By: Relevance
“…Encouraged by the results obtained with the co-culture work in SS and RA [30,31], we decided to search for the possible involvement of RVs in thyroid autoimmunity using the same approach. For our co-culture experiments, we used the H9 T cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouraged by the results obtained with the co-culture work in SS and RA [30,31], we decided to search for the possible involvement of RVs in thyroid autoimmunity using the same approach. For our co-culture experiments, we used the H9 T cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The same co-culture approach was then applied to rheumatoid arthritis (RA); virus-like particles were shown in five out of eight H9 cell preparations, two weeks after inoculation with synovial fluid from patients with active RA [31]. Following these experimental data, it was shown that over 90% of patients with SS or Systemic Lupus Erithematosus (SLE) and over 85% of patients with GD [32,33] had indeed detectable serum antibodies reactive to HIAP-1 associated proteins, compared to only a minority of disease controls and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Putative virions have been described in tissues or blood from patients with SS (161,540), multiple sclerosis (MS) (194,390), breast cancer (137), psoriasis (230), myeloproliferative diseases (66), malignant melanoma (25,50), benign osteopetrosis and sporadic para-articular osteoma (267), and thymomas (16). Similarly, retrovirus-like particles (RVLP) have been found in body fluids from patients with rheumatoid arthritis (RA) (469), SLE (480), and epidemic neuropathy (418) and in cell cultures established from individuals with testicular tumors (46,71) and chronic fatigue syndrome (192). In addition, RVLPs have also been observed in healthy human tissues and fluids including placenta (241,504) and breast milk (138,338) and in cultured cells (126,328,348).…”
Section: Electron Microscopymentioning
confidence: 98%
“…In addition, RVLPs have also been observed in healthy human tissues and fluids including placenta (241,504) and breast milk (138,338) and in cultured cells (126,328,348). Although reported as being retroviruses, such particles do not always have the expected morphology or size of retroviruses; for example, particles described in RA (469) have an apparent diameter of 200 nm, which is roughly double that expected for retroviruses, and their identity as such is therefore doubtful.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Subsequent studies that included immunoelectron microscopic examination have revealed that in five of eight RA cases, spherical particles were present. These particles had a diameter of 200 nm and a distinct eccentrically located internal core of an average size of 70 nm, and lacked epitopes for HTLV-1 pl9 and HIV-1 p24 [15]. These particles bear a striking resemblance to type C retroviral particles, but do not resemble any of the known human retroviruses, including particles derived from known endogenous retroviral structures [16].…”
Section: Retroviruses and Rheumatoid Arthritismentioning
confidence: 99%